Plywwod from plantation species: Present status and future research needs - Mathews K C; Narayanaprasad T R; Zoolagud S S (The Proceedings of National Seminar on Processing and Utilisation of Plantation Timbers and Bamboo, July 23-24 1998, IPIRTI, Bangalore, pp. 142-150., 1998)
In view of the dwindling Forest resources and non-availability of traditional timbers plywood industry in India has been experiencing acute shortage of timber for plywood manufacture. Hence studies were undertaken